A first time for everything: a true story (First Second, 2023)
"A middle grade graphic memoir based on bestselling author and Caldecott Medalist Dan Santat's awkward middle school years and the trip to Europe that changed his life. Dan's always been a good kid. The kind of kid who listens to his teachers, helps his mom with grocery shopping, and stays out of trouble. But being a good kid doesn't stop him from being bullied and feeling like he's invisible, which is why Dan has low expectations when his parents send him on a class trip to Europe. At first, he's right. He's stuck with the same girls from his middle school who love to make fun of him, and he doesn't know why his teacher insisted he come on this trip. But as he travels through France, Germany, Switzerland, and England, a series of first experiences begin to change him--first Fanta, first fondue, first time stealing a bike from German punk rockers... and first love.